Diffusion of a twentieth-century innovation - Peng, Mike; Vlas, C. (Allied Academies, 2017)
Has SWOT outlived its usefulness? by Michael D. Meeks (2016) in the pages of this Journal is a breathtaking presentation of the obvious: SWOT has shown signs of aging. While we agree with Meeks' comprehensive review and his meticulous findings, we disagree with his indictment: SWOT needs to be abandoned.